2016
DOI: 10.1001/jamadermatol.2015.5869
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Evidence of Melanocytes Isolated to the Nail Matrix

Abstract: Acquired pigmented lesions of the nail have a variety of clinical presentations and etiologies, including subungual melanoma. Previous work has suggested that melanocytes in the distal nail matrix most often develop into subungual melanoma, although there have been reports of it originating from the proximal nail matrix, hyponychium, or paronychium. 1-3 Many argue that pigmented melanomas, which excludes amelanotic melanoma, can originate directly from melanocytes in the nail bed. 1,2 However, a search of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In comparison to S‐100 protein, SOX10 antibody is characterised by both superior sensitivity and specificity in melanocytic lesions. The data for SOX10 expression in nail units are extremely scant, for it has only been assessed in a few benign longitudinal melanonychia 17 or normal nail 5 cases. Our results demonstrate the outstanding sensitivity of SOX10 in early SM (95.4%).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to S‐100 protein, SOX10 antibody is characterised by both superior sensitivity and specificity in melanocytic lesions. The data for SOX10 expression in nail units are extremely scant, for it has only been assessed in a few benign longitudinal melanonychia 17 or normal nail 5 cases. Our results demonstrate the outstanding sensitivity of SOX10 in early SM (95.4%).…”
Section: Discussionmentioning
confidence: 99%
“…The rarity of melanocytic nevi of the nail apparatus is probably due to the lower number of melanocytes within the nail unit and due to their normal quiescence 7 . Although several groups demonstrated the complete absence of melanocytes into the nail bed, 8 Perrin et al recently confirmed the presence of melanocytes within this area and showed the presence of foci in which the number of melanocytes was similar to the density of that of the matrix (about 4‐14 cell/mm) 9 …”
Section: Discussionmentioning
confidence: 99%
“…NUMs are thought to originate in the nail matrix, the primary location of melanocytes in the nail unit, where the proliferation of atypical melanocytes leads to tumor growth [ 4 ]. A study analyzing four longitudinal nail biopsies taken from a normal fingernail and the nail of an accessory digit of two male white cadavers showed that the nail matrix, not the nail bed, is the primary location of nail unit melanocytes; all four melanocyte-specific stains (Tyrosinase, MITF, Melan-A, Sox-10) identified melanocytes within the proximal nail matrix while showing a complete absence of staining in the nail bed [ 4 ]. Infrequently, NUM originates in the epithelium of the nail bed or in the epidermis of the surrounding nail [ 5 , 6 ].…”
Section: Etiologymentioning
confidence: 99%